A GLP-1:CCK fusion peptide harnesses the synergistic effects on metabolism of CCK-1 and GLP-1 receptor agonism in mice. (1st August 2018) - Hornigold, David C.; Roth, Emma; Howard, Victor; Will, Sarah; Oldham, Stephanie; Coghlan, Matthew P.; Blouet, Clemence; Trevaskis, James L.
Abstract: Combination approaches for the treatment of metabolic diseases such as obesity and diabetes are becoming increasingly relevant. Co-administration of a glucagon-like peptide-1 receptor (GLP-1R) agonist with a cholecystokinin receptor-1 (CCKR1) agonist exert synergistic effects on weight loss in obese rodents. Here, we report on the effects of a novel fusion peptide (C2816) comprised of a stabilized GLP-1R agonist, AC3174, and a CCKR1-selective agonist, AC170222. C2816 was constructed such that AC3174 was linked to the N-terminus of AC170222, thus preserving the C-terminal amide of the CCK moiety. In functional in vitro assays C2816 retained full agonism at GLP-1R and CCKR1 at lower potency compared to parent molecules, whereas a previously reported fusion peptide in the opposite orientation, (pGlu-Gln)-CCK-8/exendin-4, exhibited no activity at either receptor. Acutely, in vivo, C2816 increased cFos in key central nuclei relevant to feeding behavior, and reduced food intake in wildtype (WT), but less so in GLP-1R-deficient (GLP-1RKO), mice. In sub-chronic studies in diet-induced obese (DIO) mice, C2816 exerted superior reduction in body weight compared to co-administration of AC3174 and AC170222 albeit at a higher molar dose. These data suggest that the synergistic pharmacological effects of GLP-1 and CCK pathways can be harnessed in a single therapeutic peptide.